The given system of equations is
![\begin{gathered} x=y\rightarrow(1) \\ x-3y=4\rightarrow(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hdk2uqinslupo1qojv03t8djtcstgpzc3m.png)
To solve this system by substitution, substitute x in equation (2) by y
![y-3y=4](https://img.qammunity.org/2023/formulas/mathematics/college/sww1eqz83qz0613z7qi76vam2ncnrldbzc.png)
Now add the like terms on the left side
![\begin{gathered} (y-3y)=4 \\ -2y=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gs7yubx5mr5l4r2p5usx1ckn4h9on03dpa.png)
Divide both sides by -2
![\begin{gathered} (-2y)/(-2)=(4)/(-2) \\ y=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tzk2yvchey1idtcv0zyv60mbwhwskya3u3.png)
Substitute the value of y in equation (1) to find x
![x=-2](https://img.qammunity.org/2023/formulas/mathematics/college/hgapxsmy5hypkh6t7zmgcc8cu0ivm02dxk.png)
The solution of the system is (-2, -2)